Hay Tifton 85 grass under nitrogen doses in different days of regrowth (Acta Scientiarum. Animal Sciences, 2018)
The objective of this study was to evaluate the yield, nutritional value and potential ruminal degradation of Tifton 85 hay (Cynodon spp.) harvested at four regrowth ages (28, 35, 42 and 49 days) and fertilized with two nitrogen doses (N; 100 and 300 kg N ha-1). The experimental design was a randomized block design, arranged in a 4 x 2 factorial scheme, with six replications each. Nitrogen fertilization increased (p < 0.05) dry matter yield and digestible dry matter production of hay and also lignin and crude protein contents. Nitrogen fertilization increased (p < 0.01) the dry matter yield and the digestible dry matter production of hay, as well as lignin (p = 0.01) and crude protein (p = 0.01). The neutral detergent fiber corrected for ash and protein (p = 0.01), acid detergent fiber (p = 0.01) and cellulose (p = 0.02) adjusted to the quadratic function regression model of the regrowth ages. For potential rumen degradability hay, it was observed quadratic effect (p = 0.01) with maximum value of 73.1% at 37 days of regrowth. Tifton 85 hay fertilized with 300 kg ha -1 of N and harvested up to 37 days of regrowth results in higher hay dry matter yield, higher crude protein content, and better dry matter rumen degradability.